Rational Upscaling of a Semi-submersible Floating Platform Supporting a Wind Turbine. (September 2016) - Leimeister, Mareike; Bachynski, Erin E.; Muskulus, Michael; Thomas, Philipp
Abstract: This work examines the procedure of upscaling of a semi-submersible platform in order to support a predefined wind turbine. As a result of technological progress and design changes, basic scaling based on the turbine rating cannot be used directly. Furthermore, additional factors that floating structures have to deal with - like coupled dynamic motions, wave interaction, low frequency response and mooring system - have to be considered and included in the upscaling procedure. It is shown and discussed here, how to develop a rational upscaling process for a semi-submersible structure, under all these constraints, when the goal is to find a reasonable design of a platform, which would fit a predefined wind turbine, is producible, and has realistic dynamic behavior.